Immune Response in H. pylori-Associated Gastritis and Gastric Cancer - Qingbin Niu; Jun Zhu; Xingquan Yu; Tao Feng; Hong Ji; Yuming Li; Weiwei Zhang; Baoguang Hu (Gastroenterology Research and Practice)
Helicobacter pylori (H. pylori) is the dominant member of the gastric microbiota and has infected more than half of the human population, of whom 5–15% develop gastric diseases ranging from gastritis and metaplasia to gastric cancer. These diseases always follow inflammation induced by cell surface and intracellular receptors and subsequent signaling, such as the NF-κB pathway and inflammasomes. Some types of immune cells are recruited to enforce an antibacterial response, which could be impeded by H. pylori virulence factors with or without a specific immune cell. Following decreased inflammation, neoplasm may appear with a little immune surveillance and may inhibit antitumor immunity. Therefore, the balance between H. pylori-associated inflammation and anti-inflammation is crucial for human health and remains to be determined. Here, we discuss multiple inflammation and immunoregulatory cells in gastritis and summarize the main immune evasion strategies employed by gastric cancer.